2019
DOI: 10.1590/rbz4820180247
|View full text |Cite
|
Sign up to set email alerts
|

Performance and carcass characteristics of broilers fed whole corn germ

Abstract: The objective of this study was to evaluate the effect of including whole corn germ (WCG) on the performance; diet metabolizability; yields of carcass, cuts, and offal; and quality of meat of broilers. A total of 648 chicks were assigned to six treatments in a completely randomized design with six replicates, with 18 birds in each. Treatments consisted of a corn-and soybean meal-based control diet (0 g kg −1 WCG) and five test diets including WCG at the levels of 40, 80, 120, 160, and 200 g kg −1. Birds and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…Qi et al (2022) [29] found that maize germ meal could be included in the diets of growing ducks up to 12% without adversely affecting their growth performance, serum biochemical indexes, carcass characteristics, meat quality, or standardised ileal digestibility of amino acids. Lopes et al (2019) [24] found that the inclusion of maize germ meal in broiler diets of up to 11.8% optimized body weight gain without affecting feed intake, feed conversion ratio, metabolizable energy, carcass yields, cuts, or offal and meat quality. Maize gluten meal is produced during the wet milling of maize after the removal of starch, germ, and fibre.…”
Section: Maize By-productsmentioning
confidence: 99%
See 2 more Smart Citations
“…Qi et al (2022) [29] found that maize germ meal could be included in the diets of growing ducks up to 12% without adversely affecting their growth performance, serum biochemical indexes, carcass characteristics, meat quality, or standardised ileal digestibility of amino acids. Lopes et al (2019) [24] found that the inclusion of maize germ meal in broiler diets of up to 11.8% optimized body weight gain without affecting feed intake, feed conversion ratio, metabolizable energy, carcass yields, cuts, or offal and meat quality. Maize gluten meal is produced during the wet milling of maize after the removal of starch, germ, and fibre.…”
Section: Maize By-productsmentioning
confidence: 99%
“…In another study, improved performance, egg composition, and shell quality of layers were observed when fed diets containing 25% rice bran with 250 FTU/kg phytase additive (Habibollahi et al, 2019) [19] . In that study, the deleterious effects of phytates associated with higher rice bran inclusion levels were reversed by the phytase enzyme additive Sources NRC (1994) [27] Batal et al (2006) [8] NRC (1994) [27] Lopes et al (2019) [24] Hussain et al…”
Section: Rice By-productsmentioning
confidence: 99%
See 1 more Smart Citation
“…When corn germ dosage was 76.7 g/kg dry matter, the distribution of polyunsaturated fatty acids in lamb meat was the best [98]. Corn germ can be used at low levels in the diet of broilers without compromising their productive rates [99]. Moreover, the main processed products of corn germ by-products are as follows.…”
Section: Corn Germmentioning
confidence: 99%